Introducing Forensic and Criminal Investigation : SAGE Publications - Monckton-Smith, Jane (SAGE Publications, Ltd. (UK), 2013)
This book is a lucid and practical guide to understanding the core skills and issues involved in the criminal investigation process. Drawing on multiple disciplines and perspectives, the book promotes a critical awareness and practical comprehension of the intersections between criminology, criminal investigation and forensic science, and uses active learning strategies to help students build their knowledge. The book is organised around the three key strategic phases in a criminal investigation: - Instigation and Initial Response - The Investigation - Case Management Each strategic phase of the investigative process is carefully explained and examined. Alongside this practical approach, theoretical perspectives and academic research are laid bare for students. Introducing Forensic and Criminal Investigation is essential reading for students in criminology, criminal justice, policing, forensic psychology and related courses.